2005
DOI: 10.1063/1.1923190
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the lateral movement on the levitation and guidance force in the high-temperature superconductor maglev system

Abstract: Measuring the interaction force between a high temperature superconductor and a permanent magnet Am.Application of a high critical temperature superconductor bearing for high vacuum measurement J. Vac. Sci. Technol. A 15, 759 (1997); 10.1116/1.580816Magnetic levitation/suspension system by high-temperature superconducting materials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 11 publications
3
26
0
Order By: Relevance
“…During the measurements, the WH of the vehicle model was decreased because of the decay of the levitation force due to lateral movement [13,14], and this decay increased further with the increase of the d MLD [13] and the decrease of the WH [14]. In addition, our former investigations have shown that the vertical f RF of the vehicle model was increased as the WH was decreased [15].…”
Section: Resultsmentioning
confidence: 87%
“…During the measurements, the WH of the vehicle model was decreased because of the decay of the levitation force due to lateral movement [13,14], and this decay increased further with the increase of the d MLD [13] and the decrease of the WH [14]. In addition, our former investigations have shown that the vertical f RF of the vehicle model was increased as the WH was decreased [15].…”
Section: Resultsmentioning
confidence: 87%
“…An important related movement-direction effect was reported by Song et al 9 They experimentally found that during the cycling lateral movement for a SC in a maglev system, the levitation force continuously decreases and the rate of the decrease is gradually reduced, whereas the guidance force hysteresis curve does not change after the first cycle. After that, a large number of theoretical and numerical works have studied the changes in levitation and guidance forces when the SC moves vertically or laterally above the guideway.…”
Section: Introductionmentioning
confidence: 95%
“…The maximum speed of high-temperature superconducting Maglev is deemed to reach over 600 km/h [1], so the Maglev will displace from the center line of the permanent magnetic guideway (PMG). Other reasons, such as the thrust of wind, will lead to lateral movement and lateral movement results in the levitation force (LF) decay [2]. But change of GF above PMG during lateral movements has not been researched widely.…”
Section: Introductionmentioning
confidence: 99%
“…Del-Valle et al [5][6][7] theoretically analyzed the levitation force of a system consisting of an infinitely long superconductor over an infinitely long PMG using a realistic model, and gave the physical keys for reduction of the levitation force after lateral movement. Song et al [2] studied the levitation capability of the HTS Maglev above PMG during the lateral movements and found that LF reduces but GF keeps constant. Ma et al [8] pointed out that the pre-load method is very applicable to suppress LF decay of the bulk HTS, and this effect can be ascribed to the reduction of the hysteretic loss in the bulk HTS, i.e.…”
Section: Introductionmentioning
confidence: 99%